Grading a Music Education Graduate Student Paper - Stake, Robert E. (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
In this paper I reflect about qualitative case studies, taking as example a music education graduate student paper and the explanation I prepared in grading it. Music education is a good curricular field to illustrate that the whole is much more than the sum of its parts, and that educational interpretations emerges from inside experience, no matter how much expertise we have, e.g., in music.